2007
DOI: 10.1242/jcs.002154
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NMDA receptors increases proliferation and differentiation of hippocampal neural progenitor cells

Abstract: The prolonged effects of N-methyl-D-aspartate (NMDA) receptor activation on the proliferation and differentiation of hippocampal neural progenitor cells (NPCs) were studied. Under conditions of mitogen-mediated proliferation, a single NMDA pulse (5 μM) increased the fraction of 5-bromo-2-deoxyuridine (BrdU)-positive (BrdU+) cells after a delay of 72 hours. Similarly, a single systemic injection of NMDA (100 mg/kg) increased the number of BrdU+ cells in the dentate gyrus (DG) after 28 days, but not after 3 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 31 publications
6
64
2
Order By: Relevance
“…Neurospheres derived from the embryonic rat brain express the NR1 and NR2B subunits of the NMDA receptor and show reductions in diameter and number (Mochizuki et al, 2007). Furthermore, the activation of NMDA receptors increases the proliferation of neuronal progenitors in the developing hippocampus (Joo et al, 2007) and striatum (Luk et al, 2003) as well. These findings are consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Neurospheres derived from the embryonic rat brain express the NR1 and NR2B subunits of the NMDA receptor and show reductions in diameter and number (Mochizuki et al, 2007). Furthermore, the activation of NMDA receptors increases the proliferation of neuronal progenitors in the developing hippocampus (Joo et al, 2007) and striatum (Luk et al, 2003) as well. These findings are consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA has been shown to promote the proliferation and differentiation of hippocampal neural progenitor cells (NPCs) in vitro by activating NMDA receptors [9] . NMDA is mitogenic for MC3T3-E1 osteoblastic cells and glutamate has been reported to promote the viability of primary human osteoblasts in vitro [10] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Joo and colleagues [66] have shown that proliferation is positively regulated by NMDAR activity in the embryonic hippocampus, and similar results have been shown in the P0 hippocampus [72]. On the other hand, treatment of P0 cultures with Ro 25-6981 or MK801 can significantly decrease neurosphere formation [72].…”
Section: Direct Modulation Of Nmdars Alters Nspc Proliferation In Thementioning
confidence: 63%
“…Instead, continuous activation of the NMDAR is more likely to shut down actively proliferating stem cells to protect them from NMDAR-mediated excitotoxicity. Indeed, some in vitro studies have used sustained concentrations of NMDA that were shown to cause excitotoxic death of the NSPCs (e.g., [66]), so it is not surprising that proliferation of NSPCs can be inhibited under these conditions. Nevertheless, other studies report that cell death is not induced by the NMDA treatment (e.g., [62]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation